Silver Sulfide Nanostructures: Synthesis and Characterization - Ahmed, Afrah; M. Al Hindawi, Aula; M. Shiltagh, Nagham (Pure Sciences International Journal of Kerbala, 2024)
Ag2S semiconductor nanoparticles were prepared successfully using the chemical precipitation method. The XRD pattern shows that the Ag2S particles are crystalline with a monoclinic phase. "Debye-Scherrer" formula was used to calculate the crystal size and it was found to be 64.22 nm. According to FE-SEM images, all particles have a spherical shape. The band gap for Ag2S was estimated from the optical absorption curve and it was 3.89 eV.